Anti-aging and redox state regulation effects of A-type proanthocyanidins-rich cranberry concentrate and its comparison with grape seed extract in mice. (March 2017) - Jiao, Jingjing; Wei, Yan; Chen, Jingnan; Chen, Xinyu; Zhang, Yu
Highlights: A-type proanthocyanidin-rich cranberry concentrate has promising anti-aging effect. Cranberry concentrate is capable of improving glutathione peroxidase activity. Grape seed extract is able to increase superoxide dismutase activity. Both products regulate malonaldehyde, monoamine oxidase and 8-isoprostane levels. Neither of products generates any positive effect on catalase activities. Abstract: We investigated the anti-aging and redox state regulation effects by A-type proanthocyanidins (PACs)-rich cranberry concentrate (CBC) and its comparison with B-type PACs-rich grape seed extract (GSE). Using the Q-Extractive mass spectrometry, PACs dimer A and B were identified as predominant phenolic compounds of CBC and GSE, respectively, while epicatechin was present in both extracts. Using thed -galactose-induced aging mice model, effects were investigated via an 8-week oral gavage considering water-soluble vitamin E as the positive control. Both CBC and GSE reduced hepatic and brain thiobarbituric acid reactive substances, and plasma 8-isoprostane levels by 30–57%, 24–30% and 11–62%, respectively, and decreased brain and plasma monoamine oxidase activities by 27–59% and 65–71%, respectively. CBC could improve hepatic glutathione peroxidase activity by 42%, while GSE increased hepatic superoxide dismutase activity by 13%. Therefore, both extracts exerted anti-aging effects probably via regulating in vivo redox state. However, neither generated any effect on catalase activities.